Effects of Different Gasoline Additives on Fuel Consumption and Emissions in a Vehicle Equipped With the GDI Engine - Wen, Mingsheng; Yin, Zenghui; Zheng, Zunqing; Liu, Haifeng; Zhang, Chuanqi; Cui, Yanqing; Ming, Zhenyang; Feng, Lei; Yue, Zongyu; Yao, Mingfa (Frontiers in Mechanical Engineering, 2022)
Fuel additives are considered to be a cost-effective and simple approach to improve combustion and reduce the harmful emissions of internal combustion engines. In addition to the use of conventional fuel additives, some unconventional fuel additives also have potential to improve fuel properties. Exploring the effects of different unconventional additives can provide a valuable reference to improve vehicle performance by fuel optimization. In this study, five unconventional gasoline additives (i.e., isopropyl ether, aniline, diethylamine, dimethyl malonate and p-tert-butylphenol) were blended with the baseline gasoline (G92). The five blended fuels are referred to as G92-1, G92-2, G92-3, G92-4, and G92-5, respectively. Fuels with different additives were tested on a compact passenger vehicle with a 1.4-L gasoline direct injection engine to assess the effects of these additives on performance and emission characteristics, and G92 gasoline was compared as a baseline. The new European drive cycle (NEDC), which is representative for passenger car and light duty vehicles, was chosen in the tests. The experimental results show little or slight improvement in fuel consumption for fuels blended with additives. With respect to gaseous emissions, the vehicle obtains the lowest and highest NOx emissions by fueling G92-5 (blended with p-tert-butylphenol) and G92-3 (blended with diethylamine), respectively; the lowest and highest CO emission is acquired using G92-2 (blended with aniline) and G92-4 (blended with dimethyl malonate), respectively; the vehicle reaches the lowest and highest THC emissions when fueling G92-3 (blended with diethylamine) and G92-4 (blended with dimethyl malonate), respectively; and the lowest and highest CO2 emission using G92-3 (blended with diethylamine) and G92-2 (blended with aniline), respectively. Compared with the baseline gasoline fuel, all of the fuels with additives show improved engine-out PM emissions. Furthermore, all five additives can improve the acceleration performance slightly. In brief, diethylamine is potential gasoline additive to reduce carbon emissions, improve fuel consumption, and enhance performance.